A Retrospective Clinico-Pathologic Study of 35 Dogs with Urethral Transitional Cell Carcinoma Undergoing Treatment - Giulia Ghisoni; Armando Foglia; Silvia Sabattini; Chiara Agnoli; Francesco Dondi; Simone Perfetti; Laura Marconato (Animals, 2023)
Chemotherapy and cyclooxygenase inhibitors (COXi) are primary treatments for canine urethral transitional cell carcinoma (uTCC), a tumor known for its aggressiveness and poor prognosis. This retrospective study aimed to evaluate the clinico-pathological characteristics, treatment modalities, and prognostic factors of 35 dogs with confirmed uTCC that received chemotherapy and COXi. Upon admission, urethral obstruction (UO) and urinary tract infection (UTI) were observed in seven (20%) dogs each. Gemcitabine (n = 20; 57.1%) and vinblastine (n = 10; 28.6%) were commonly used as first-line therapies, with four dogs also receiving radiation therapy. Based on RECIST, one (2.9%) dog achieved complete remission, nine (25.7%) partial remission, 20 (57.14%) showed stable disease, and five (14.3%) progressed. Among dogs with UO, six (85.7%) showed resolution or improvement after the first chemotherapy dose. The median time to local progression was 171 days (range: 107–235), and the median survival time was 333 days (range: 158–508). Dogs with UO upon admission had a higher risk of local progression, while both UO and UTI were associated with an increased risk of overall disease progression and tumor-related death. Additionally, gemcitabine significantly improved metastatic control. This study identified UO and UTI as negative prognostic factors, highlighting the importance of a multimodal approach in managing uTCC.